Political Reforms for Prosperity and Political Resistance in Botswana (Asian Journal of Social Science Studies, 2017)
A people thought to be passive, weak and docile surprised many when they revolted against encroaching authoritarianism in their country - Botswana. What started under Ian Khama as the most feared and potentially productive regime turned out to be the most opposed and most beleaguered. How did this reverse happen? Many authors (including Good, Taylor and others) mistakenly assumed that Botswana’s civil society was too weak and fearful, and that it would not stand up to any dictatorship. In contrast, Botswana towards the end of 2011 had reached a point at which civil society constantly challenged and clashed with government, resisting growing authoritarian tendencies. The political scenario of mid 2011 characterised by a long drawn public service strike was the clearest signal that the president was no longer feared. This paper focuses on Khama’s political reforms and the political resistance that accompanied them. It argues that Ian Khama introduced several reforms that met lots of resistance that threatened the stability and sustainability of the Botswana society. The paper concludes that political reforms have left the Botswana society deeply divided, but alert.